Biodiesel from Avocado Seed Oil with CaO and CaO Super Basa Catalyst from Egg Shell Waste - Devy Susanty; Choerunnas, Paqih; Nurhayati, Lany; Wardhani, Gladys Ayu Paramita Kusumah (Universitas Nusa Bangsa, 2024)
One waste that can be used as raw material for biodiesel is avocado seeds. Generally, biodiesel from avocado seed oil is synthesized using a homogeneous base catalyst, NaOH or KOH. However, the yield of Free Fatty Acids (FFA) is still low, so it is necessary to make biodiesel using heterogeneous base catalysts such as calcium oxide (CaO) and super base CaO from eggshell waste. Avocado seed oil biodiesel was synthesized using the method of transesterification with a ratio of 1:6, and a super base CaO/CaO catalyst of 1.5% (w/w) of the weight of avocado seed oil was added. The use of the CaO catalyst produced a Fatty Acid Methyl Ester (FAME) of 98.21% with a biodiesel yield of 73.77%, while the use of a super base CaO catalyst produced a FAME of 98.47% with a biodiesel yield of 74.50%. Characterization of biodiesel using FTIR shows the presence of methyl, ether, alcohol, carbonyl, and ester functional groups (C=O and C-O bonds), which are characteristics of the resulting biodiesel trans-esterification. Based on the yield and physical and chemical properties, the avocado seed oil biodiesel produced is better using the super base CaO catalyst than the CaO catalyst.